Toward Public Bioethics? - Kaebnick, Gregory E. (The Hastings Center report, 2017)
This issue of the Hastings Center Report (May-June 2017) features a couple of interesting takes on the governance challenges of emerging technologies. In an essay on the National Academies of Science, Engineering, and Medicine report published this February on human germ-line gene editing, Eric Juengst, a philosopher at the University of North Carolina, argues that the NASEM committee did not manage to rethink the rules. Juengst reaches what he calls an “eccentric conclusion”: “The committee's 2017 consensus report has been widely interpreted as ‘opening the door’ to inheritable human genetic modification and holding a line against enhancement interventions. But on a close reading it does neither.” In the column Policy and Politics, Sarah Chan, a chancellor's fellow at the University of Edinburgh, discusses the emerging science of “organoids,” “embryoids,” and “synthetic human entities with embryo-like features” and calls for a sustained effort to rethink the rules for embryo research.